Immunoglobulin heavy chain constant regions regulate immunity and tolerance to idiotypes of antibody variable regions - Reitan, Solveig Klaebo (The National Academy of Sciences, 2002)
Particular syngeneic adjuvant-free monoclonal antibodies are immunogenic and elicit antibody responses against the variable region idiotypes (Ids). We here study how heavy-chain constant regions (C(H)) regulate immune responses to Ids of free, uncomplexed monoclonal antibodies. To this end, we selected two hybridomas, called Id(3) and Id(A.01), that produce immunogenic IgMλ2 directed toward 2,4,6-trinitrophenyl, and subcloned rare IgG1, IgG3, IgE, or IgA class switch variants. The purified switch variants, which possessed the Ids of their IgM progenitors, were injected repeatedly without added adjuvant into BALB/c mice, and anti-Id IgG responses were determined. These repeated injections revealed that the immunogenicity of Ids was lost by switching to IgG1 and IgG3, restored when the Fc piece of IgG1 was removed, maintained by switching to IgE and monomeric IgA, and lost in polymeric IgA. Loss of immunogenicity was associated with acquisition of Id-specific tolerogenicity, as determined by immunization challenge with Id borne by IgM. An Id borne by IgG induced tolerance when injected at least 90 days before or 3–21 days after immunization with IgM Id was begun. Ids of IgG were also tolerogenic in mice deficient in FcγRIIB or FcγRI + III. The results suggest that Ids that have switched to IgG and pIgA negatively control immune responses to shared Ids, including the Ids of their IgM progenitors.